Respons Getaran Non-Linier pada Sistem Poros-rotor Bagian II: Kaji Banding Metode Runge-Kutta dan Metode Deret Fungsional Volterra - Tegoeh Tjahjowidodo; Komang Bagiasna; Zainal Abidin (Institute for Research and Community Services (LPPM) ITB, 2000)
Sari. Bantalan gelinding digunakan secara luas sebagai pemompa pada setiap mesin rotasi. Oleh karena itu, karakteristik dinamina suatu bantalan harus dapat diketahui dengan baik. Karakteristik dinamik bantalan yang diketahui dapat digunakan untuk menganalisis respons getaran yang terjadi pada struktur yang menggunakan bantalan tersebut. Sayangnya mekanisme kontak pada bantalan mengakibatkan kekakuan yang tidak linier pada bantalan. Hal ini mengakibatkan bantalan gelinding merupakan system getaran non-linier. Analisis FRF Non-Linier dapat dilakukan dengan memanfaatkan deret Voltera. Dalam penelitian ini deret Voltera digunakan untuk menentukan FRF Non-Linier dari bantalan yang diamati sehingga dapat diramalkan respons getarannya pada frekuensi harmonic akibat sinyal pengeksitasi. Non-linear Vibration Respons of Bearing System Part II: Comparative Study of Runge-Kutta metho and Volterra-functional-series methodAbstract. Rotating machinery is commonly utilized in the processing industry. Vibration monitoring based on predictive maintenance technology is widely utilized for condition monitoring of the rotating machinery in service. This maintenance technology is based on the signature of the vibration response normally measured at the bearing house. On the other hand, the vibration response of a system is determined by the system dynamic characteristic and its working stimulus. Therefore the nature of the main component dynamic characteristics results in significant influence on the predicted vibration response at the bearing house. As mentioned above the signature of the vibration response measured at the bearing house and presented in the frequency domain contains several harmonic signals. Most of the higher harmonics do not have physical meanings, but they exist in the vibration measurement results and confused the researchers. Regarding those harmonic signals a hypothesis can be developed for identifying its origin. They are assumed to be generated due to dynamic characteristic non-linearity of the vibration system combined with the stiffness non-linearity of the roll bearing. By analyzing harmonic signal response due to nonlinear property of the vibration system, hopefully the mechanical signature of nonlinear vibration system can be generated. Therefore, many other mechanical signatures of components failure can be formulated and the harmonic signals, which are usually occurred, can be predicted more accurately.